Distributed cooperative information bottleneck - Vera, Matias; Rey Vega, Leonardo; Piantanida, Pablo (Proceedings / IEEE International Symposium on Information Theory, 2017)
This paper investigates a scenario where two distant nodes separately observe memoryless process, namely X 1 and X 2 , and can cooperate through multiple exchanges of messages with the goal of enabling a third node to learn "relevant information" (measured in terms of a multi-letter mutual information) about some hidden memoryless process Y, which is arbitrarily dependent on (X 1 , X 2 ). These interactive exchanges yield an explicit cooperation that helps the third node to identify, from the distributed observations X 1 and X 2 , useful features for the inference of Y. An inner and an outer bound to the rate-relevance region of this problem is derived. Optimal characterization of the rate-relevance region under two different conditions on the dependence structures of the involved variables is showed. Also, two examples for Gaussian sources are studied.